THE IMPACTS OF THE COVID-19 PANDEMIC ON THE TOURISM SUPPLY CHAIN SYSTEM IN KRABI PROVINCE - Panich, Tanompong; Srithongphim, Wanlapha (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2021)
The objectives were to study the strengths, weaknesses, opportunities, and obstacles of the tourism supply chain and to study tourism strategies in the tourism supply chain system during the Covid-19 crisis between January and March 2020. Samples were of 400 tourists and 30 Tourism Supply Chain specialists. Data collection was made through a questionnaire survey and in-depth interviews. The data analysis employed descriptive and inferential statistics as well as content analysis. The results showed that the strengths of tourism supply chains in Thailand consist of 1) price compared to received services, 2) quality of serviced personnel and 3) quality of products or services, respectively. In terms of weakness, the issue includes communication styles in foreign languages. In terms of opportunities, the issues include 1) tourist destination reputation and beauty, 2) diversity of tourism activities, and 3) online media growth. Lastly, the obstacles include 1) attractiveness of tourist destination in other provinces, 2) lack of mutual support during supply chains, and 3) safety standards for tourists. For the appropriate strategy in the tourism supply chain, the findings were as follows: 1) marketing communication should focus on local identity, 2) tourism personnel should be upskilled and reskilled, 3) technology to communicate via social media should be well considered, and 4) there should be a promotion on tourists’ health safety standards. In addition, the future research is also discussed.